El parecer de Agustín sobre el amor como gracia, en la controversia con Juliano de Eclana - Lamberigts, Mathijs (Augustinus, 2017)
During the Pelagian controversy, the precise relation between grace and free will was an important issue. Augustine emphasized the priority of grace over human beings' free will after the Fall. Pelagians such as Julian of Aeclanum were of the opinion that such view annihilated human beings' free will. Throughout history, time and again, scholars belonging to different schools and denominations have discussed this issue at length. In this article, we concentrate on Augustine's view on love as grace during his debate with Julian. We argue that one should broaden the scope of this question and pay attention to the role of divine !ove as an important and decisive factor with regard to the proper activity of grace in the redemption and liberation of human beings. Thinking the relation between human beings and God in terms of love is a help in order to overcome the unfruitful grace-freewill antinomy. In fact, such approach does justice to both the Scriptural sources of Augustine's position and the bishop's spiritual view on the topic under consideration.